दुलारी उपन्यासमा दलित प्रतिनिधित्व - Guru Prasad Pokharel (Tribhuvan University Journal, 2026)
In the novel Dulari (2076 BS), the author portrays the struggles of Nepal’s Dalit community and shows how much they suffer because of old-school upper-caste attitudes in everyday life. The story uses Nepali people’s everyday traditions and mindsets to show the heavy emotional toll. This creates a vivid picture of the deep-rooted inequalities within the society. This study analyses the texts to explore how the Dalit community is portrayed in the novel and how the caste system uses power and control to keep the Dalit community down. The so-called upper castes act arrogantly and control, while the lower caste communities face exploitation. This study highlights the feudal ideologies and caste-based oppression in the community. In the book, we see a brutal truth of upper-caste people using their power and social status to scheme against lower-caste people by taking control of their property, homes and forced labor for their own gain in the name of caste. This greed made life between the castes completely unfair and toxic. The people belonging to lower castes are shown as neglected, voiceless, powerless, and socially vulnerable. By dividing Nepali society into the traditional caste system into ’high’ and ’low’ groups, it unknowingly made the discrimination acceptable. Because the powerful ’upper caste rulers’ controlled all the jobs, lands and money, they made this unfair treatment seem normal. They used their power to steal from the poor. In the end, this constant discrimination didn’t just make the Dalit community poor; it caused them deep emotional and mental pain.